Intranasal findings in unilateral primary acquired nasolacrimal duct obstruction - Thakur, Sanjeev Kumar; Yadav, Baleshwar; Bedajit, Raj Kumar; Agrahari, Akash; Singh, Sanjay Kumar; Afaque, Anwar (Journal of Chitwan Medical College, 2019)
Background: Primary acquired nasolacrimal duct obstruction (PANDO) is a common entity with associated different types of intranasal abnormalities. The pathogenesis of PANDO is unknown. The objective of the study was to describe the intranasal findings in cases of PANDO and find out any association of these findings to the disease. Methods: A comparative cross-sectional study was designed consisting of 50 cases of unilateral PANDO with epiphora and 50 normal volunteers with no history of epiphora. Nasal Evaluation was done with anterior rhinoscopy and nasal endoscopy. Data was tabulated and analyzed using SPSS version 21. Results: The mean age in the unilateral PANDO group was 33.6 years and 34.5 years in the normal volunteer’s group (P-0.84). Left sided dominance of PANDO was observed in 64% (32/50) cases. The odds of having Nasolacrimal duct (NLD) obstruction was1.6 times more among individuals having septal deviation versus no deviation (95% CI, 0.907–2.78). The laterality of septal deviation was corresponding to the side of NLD obstruction in 91% (31/34) cases. High located DNS was more common in the PANDO group which was significant (P-value 0.012). Turbinate hypertrophy, the presence of septal spur or rhinitis had no significant association with NLD obstruction. Conclusions: Deviated nasal septum (DNS), turbinate hypertrophy, septal spur and rhinitis were the associated intranasal findings in cases of unilateral PANDO. A significant association exists between DNS and PANDO, although a cause and effect relation require further probing.